The influence of cardiopulmonary bypass operation on the biodistribution of 99mTc-HMPAOlabelled granulocytes - Evaluation in pigs by planar scintigraphy and section-analyses - Happel, Christian (2012)
Aim of the study was to evaluate the influence of an extra corporal perfusion (cardiopulmonary bypass operation - cpb) on activation and biodistribution of 99mTc labelled granulocytes in pigs with and without inhibition of the granulocytes by a leukocyte inhibition module (LIM). The cpb is often related to an activation of granulocytes resulting in an inflammatory answer. The biological mechanisms are unsolved yet. First trials of our group showed that LIM may inhibit the activation of neutrophils and therefore antagonize a cpb-caused impairment of cardiac function. This study is the continuation of these experiments with a higher number of animals and the focus on scintigraphic imaging. Animals, material, methods: 39 German landrace pigs were subdivided into three groups: group A (control) median sternotomy without cpb, group B with cpb, group C with LIM in addition to cpb. After labelling with 99mTc-HMPAO autologues granulocytes were reinjected. Subsequently to cpb, the animals underwent scintigraphic imaging. Quantification was performed with ROI evaluation and with tissue samples (section analysis) examined in a well counter. Results: A high uptake of 99mTc-HMPAO was found in the liver. The count rates in brain, heart, lung, spleen and kidneys were far below. The amount of 99mTc-activity in the organ related to the half life corrected administered activity [%] was for the tissue samples (group A/B/C): brain 0.01/0.02/0.03; lung 12.1/8.3/11.5; heart 0.35/0.54/0.42; kidney 1.24/0.87/1.02; spleen 4.0/4.0/4.5, liver 16.8/20.9/19.6. The count rates determined by ROI-evaluation of the scintigraphic images related to the total count rate in the image [%] were (group A/B/C): brain 1.1/0.9/1.0; lung 15.6/10.4/12.2; heart 4.0/3.5/3.4; kidney 4.0/2.9/3.2; spleen 7.6/7.7/9.5, liver 23.1/36.7/31.4. A significant difference in the tracer uptake between the groups could neither be detected by scintigraphic imaging nor evaluation of tissue samples. Conclusion: Scintigraphic imaging as well as section analysis showed a comparable biodistribution of the tracer. Therefore, the initial results of our group were not confirmed with a considerably higher number of animals. © Schattauer 2012.